A STUDY ON THE â€œABSTRACTIVE (IDEAL) PLURALITY OF CRIMESâ€ IN IMAMIA JURISPRUDENCE AND IRANIAN LAW Ø¯ÙˆØ±Ù‡51 Ø´Ù…Ø§Ø±Ù‡4 Ø³Ø§Ù„1398 - ?????, ?????????; ??????, ??????? (??? ? ????)
?Abstractive or ideal plurality? of crimes is a general cause of aggravation of punishment and terminologically it is the application of multiple criminal titles to a single act. This issue is of special significance in criminal law since determination of a punishment proportionate to the committed crime leads to compliance with human and Islamic principles such as criminal justice and proportionality of crime and punishment and as a result, the mental safety of society is ensured. The Iranian legislator, like a number of legal scholars, has accepted the ideal plurality of crimes theory, adopting the application of multiple punishments in some cases and their overlap in others. Given the Imamia jurists' opinions, it appears that where, in case of ideal plurality, a crime is committed against a limb or the soul or the limb and profit, the punishments overlap and the more blood money is specified and in case qisas for life and for other limbs or profits overlap, only qisas for life is administered according to the purported signification. But in cases such as crime leading to blood money for two limbs or two lives and the like, given the absence of text and the impossibility of extending the available texts to cases not mentioned therein and the principle of non-overlap, determination of multiple punishments may be justified. The conclusion is that the principle of criminal justice which is deducted from intellect and sharia has not been complied with in certain articles of law considered in this paper and the Islamic penal code needs to be amended.